Leisure time management in Marmara university and_x000D_ Kilis 7 aralik university students training in sports_x000D_ sciences - ALPULLU, AYTEKİN (My University, 2019)
This sport science research in an undergraduate Faculty of Marmara University Sports Science and Kilis 7 Aralık Universityof Physical Education and Sports School students of “Leisure Management” ideas are evaluated.Free time management scale;Wei-Ching Wang et al. (2011) and Akgül and Karaküçük (2015) by adapting to Turkish by making validity and reliabilitystudy consists of 15 items and 4 sub-dimensions. 285 students from Marmara University Faculty of Sport Sciences and Kilis 7Aralık University School of Physical Education and Sports participated in the study. In data analysis, descriptive statistics, ttest, ANOVA test were used. As a result of the statistical analysis, it was seen that the majority of the participants consisted ofMarmara University students, while in the departments, there was a larger number of male students. In the other findings, itwas understood that there was more participation in the 18-20 age group, they were single in marital status and they weremore in the 1st class and they participated in their activities in leisure time 2-3 days a week. While there was a significantdifference between the total scale scores of the participants and the variables of the universities, it was found that there wasno significant difference in gender, marital status variables. There was a significant difference between the scale subdimensions and the activities of universities, age, leisure time and classes. As a result, it is understood that leisure time isbetter managed in metropolitan cities and that students who are studying in the field of sports should be directed to leisuretime activities.